IMPLEMENTATION OF THE PDCA CYCLE IN THE FURNITURE INDUSTRY: : challenges and benefits for continuous improvement in the context of production operations - Silva, Vanessa Pereira de Lima da; Casagrande, Diego josé (Revista Interface Tecnológica, 2024)
This article aims to analyze the implementation of the PDCA Cycle in the furniture industry, focusing on the challenges and benefits that this methodology offers to the sector. The study adopts a bibliographic approach, reviewing the existing literature on PDCA and its use in different industrial contexts, with an emphasis on product customization in the furniture industry. The research identifies that, when applied correctly, PDCA provides significant improvements in operational efficiency, waste reduction, and product quality enhancement. However, the study also highlights challenges such as resistance to change and the need to adapt the methodology to processes requiring flexibility, particularly in industries that operate on-demand. The conclusion suggests that, despite these obstacles, PDCA can be an effective tool for continuous improvement, as long as companies invest in training and adapt their practices to the specific demands of the furniture market.